The effectiveness of gluten-free dietary interventions: A systematic review - Poslt Königová, Michaela; Sebalo Vňuková, Martina; Řehořková, Petra; Anders, Martin; Ptáček, Radek (Frontiers in Psychology, 2023)
Coeliac disease is a chronic autoimmune type of gastroenterological disorder in which the digestion of gluten leads to damage and constant inflammation of the small intestine. Moreover, there are associated physical and mental health problems related to coeliac disease, i.e. lower health-related quality of life, depression and anxiety. The only effective treatment for coeliac disease is lifelong adherence to a gluten-free diet. However, researchers suggest that strict adherence to a gluten-free diet ranges from 42 % to 80 %, depending on the definition and method of assessment. This review examines interventions designed for those that need to adhere to life-long diet measures and their success in terms of gluten-free adherence and change in the health-related quality of life. In April 2022, Scopus, Web of Science, PubMed and ProQuest databases were searched using the following terms: “coeliac disease” AND “celiac disease” AND “gluten free diet” AND “intervention” AND “health related quality of life” AND “diabetes”. Eight studies were suitable for this review. They analysed different intervention techniques and their impact on gluten-free diet adherence, quality of life, and the reasons for not following the diet. Studies showed statistically significant improvements in the knowledge base regarding coeliac disease and gluten-free diet, diet adherence and quality of life satisfaction right after the intervention and three months follow-up. Some studies also focused on behavioural and cognitive aspects of non-adherence to diet measures.